Integrating Critical Discourse Analysis into English Teaching Materials: A Critical Pedagogical Perspective - Rahmi Kusno; La Aba; Adimawati Helingo; Jhems Richard Hasan; Zulkifli Akhmad (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study explores the integration of Critical Discourse Analysis (CDA) into English teaching materials to promote students’ critical literacy and engagement in English as a Foreign Language (EFL) learning. The study addresses the problem that English teaching materials often prioritize linguistic competence while paying limited attention to critical awareness of ideology, power relations, and social meanings embedded in texts. The purpose of this study is to examine how CDA principles are integrated into English teaching materials and to identify classroom activities that support students’ critical discourse awareness. A qualitative case study design was employed in one Indonesian senior high school involving one English teacher and twenty Grade 11 students. Data were gathered through document analysis, classroom observations, and semi-structured interviews. English textbooks, teacher-developed materials, and supplementary texts served as the primary data sources. The data were analyzed using thematic analysis to identify recurring patterns related to classroom implementation, student engagement, and learning challenges. The findings indicate that CDA was mainly integrated through interactive and student-centered activities, including discussions, open-ended questioning, and role plays, rather than through systematic discourse analysis. Students generally demonstrated positive responses, increased participation, and emerging critical awareness, although differences in language proficiency and confidence remained significant challenges. The study highlights the pedagogical value of integrating CDA into EFL instruction to foster critical literacy and reflective learning. Its originality lies in providing empirical evidence from an Indonesian secondary school context, contributing to the growing discussion on critical pedagogy and socially responsive English language teaching.